Exploring english language needs: Non-english major students at University of Al-Qolam Malang - Mulis, Mulis; Blouin, Aberald (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This research investigated English language needs for new students majoring in non-English who are taking courses in the Foreign Language Center program. This research approach used qualitative with descriptive methods. The subjects in this research were new students majoring in non-English. The data in this research was obtained through two stages, namely Focus Group Discussion (FGD) involving six students who were representatives from each study program; Indonesian Language Tadris, Mathematics Tadris, Islamic Religious Education, Sharia Economic Law, Ahwal Al-Shakhsyiyyah, and Islamic Teaching Communication, and distribution of questionnaires filled in by 127 students. Here the researcher found that most students (75%) who took part in the Foreign Language Center (English) program wanted to master all English language skills; listening, speaking, reading, and writing. Apart from that, the English components they need are vocabulary and grammar with a percentage (78%). Furthermore, regarding the abilities and components of English, students want the lecturer's strategy used in the learning process to be text-based teaching. Therefore, researchers provide recommendations so that learning is implemented using relevant methods such as the Grammar Translation Method (GTM), Direct Method (DM), Audio Lingual Method (ALM), and Communicative Language Teaching Method (CLT).